Internship Tracer Survey Report Internship Innovation Grant (I2G) - Makungwe, Mirriam; Mutenje, Munyaradzi; Pele, Winnie; Jacobs-Mata, Inga (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This tracer survey was carried out to assess the effectiveness of the internship program, to what extent have the capacity of young Zambians that participated in the internship program have their skills, capacity and network been strengthened.